PERCEIVED WAYS OF DIAGNOSTIC HELP OPTIMISATION TO PATIENTS WITH SYMPTOMATIC EPILEPSY ON CHRONIC HERPESVIRUS ENCEPHALITIS - N. A. Shnayder; N. I. Kamzalakova; S. V. Krijanovskaya; Yu. S. Panina (Эпилепсия и пароксизмальные состояния, 2016)
The aim of our research was search of possible ways to optimize the diagnostic care for patients with symptomatic focal epilepsy with chronic parainfectious encephalitis associated with viruses of the family Herpes viridae. Materials and Methods. The study included 180 patients (107 women and 73 men) aged 18 to 50 years. Diagnostic methods include analysis of objective and subjective neurological symptoms, video-EEG monitoring, multimodal evoked potentials, brain MRI, laboratory methods (hemogram, immunogram, antibody titers of IgG and IgM to antigens of viruses HSV-1, HSV-2, CMV, VZV, HHV-6 and EBV, antibody avidity). Results. Relapsing course labial / facial herpes with subacute course was recorded in 93.1% of patients without epilepsy versus 95.7% patients with epilepsy (φ=0,764, p>0.05). Patients had a combined lesion of the central and peripheral nervous system involvement in the pathological process of II and VIII of the pairs (usually), V and VII pairs of cranial nerves (rarely), and the presence of chronic diseases of the paranasal sinuses in the form of chronic hyperplastic sinusitis. Patients with epilepsy, the total concentration of the major classes of immunoglobulins was smaller compared with uncomplicated encephalitis (IgA – 1,12 g/l vs. 1,5 g/l; IgG – 10,3 g/l vs. 13.8 g/l). This indicates a highly probable functional deficiency of B-lymphocytes and is manifested in the reduction antiteloproduktsii that promotes slow accumulation of specific antibodies, chronic process, an increase in viral load and associated complications. Reduced visual afferentation was 65.5% cases of encephalitis without epilepsy vs. 62.4% encephalitis with epilepsy. Reduced hearing afferentation observed less frequently (24.1% vs. 26.9%, respectively). Changes in cognitive evoked potentials identified in 28.7% cases of encephalitis without epilepsy vs. 53.8% encephalitis with epilepsy. Conclusions. Possible ways to optimize the diagnostic care for patients with symptomatic epilepsy parainfectious include a multidisciplinary approach (neurologist, neuroscientist, epileptologist, immunologist, otolaryngologist, ophthalmologist, psychotherapist), immune status, serum antibodies to herpesviruses, video-EEG monitoring, multimodal evoked potentials, neuropsychological testing, brain MRI with contrast, MR spectroscopy mediobasal (limbic) parts of brain.